Population Status, Diurnal Activity Pattern, Feeding Ecology, and Habitat Association of Colobus Monkey (Colobus guereza) in Saja Forest, Kaffa Zone, Southwest Ethiopia. (13th October 2022) - Mola, Misganaw; Ayiza, Aklilu; Asnakew, Muluye; Abuye, Tiruye
Abstract : Colobus monkeys ( Colobus guereza) are endemic to the Ethiopian plateau, distributed in different ecological habitats such as moist and deciduous forests, savanna woodlands, and montane forests. The population status, diurnal activity pattern, feeding ecology, and habitat association of Colobus guereza were investigated in Saja Forest, southwest Ethiopia, from June 2019 to February 2020, covering both wet and dry seasons. A total of 39 different types of transect were systematically established, distributed in both dense forest and in shrubland. Data were collected for 60 days in total across a wet and a dry season, both at dawn and in the afternoon. A total of 246 ± 39.1 individuals were recorded, of which 132 ± 24.4 and 114 ± 14.7 individuals were recorded during the wet and dry seasons, respectively. The population and group sizes did not statistically differ between the wet and dry seasons but shrubland habitat had fewer individuals and smaller groups than forest. Out of the recorded Colobus guereza, 33.5% were adult males, 34.5% were adult females, 28% were sub-adult males, 14.5% were sub-adult females, and 12.5% were juveniles/young. Feeding (29.5%) and resting (19.5%) were the most recorded daily activities for Colobus guereza . Young leaves were the largest (31%) contributor to the diet followed by mature leaves (22%) in both seasons. Other common dietary items were shoots (20%), barks (13%), fruits (11%), and flowers (3%). Colobus guereza were observed feeding on a diverse diet of 26 plant species belonging to 21 genera within 21 families. The habitats of these primates are currently diminishing due to anthropogenic activities such as agricultural expansion, human settlement, livestock grazing, and other forms of human wildlife conflict. Furthermore, guerezas are hunted for their skin and are also major sources of meat for the Menja people in the study area. Therefore, awareness creation for local people towards wildlife conservation is needed.